2006
DOI: 10.4141/s05-048
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Illinois Soil Nitrogen Test to liquid and composted dairy manure applications in a corn agroecosystem

Abstract: Response of the Illinois Soil Nitrogen Test to liquid and composted dairy manure applications in a corn agroecosystem. Can. J. Soil Sci. 86: 655-663. Dairy manure is important for corn (Zea mays L.) production in New York. Optimizing corn yield while minimizing environmental loss with manure nutrients is often a challenge. A potential tool for improving N management is the Illinois Soil Nitrogen Test (ISNT), which estimates amino sugar N, a pool of potentially mineralizable N for corn uptake. The objectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
(16 reference statements)
0
13
3
Order By: Relevance
“…In this case, r values between soil N and N up are not different among the methods (hot water, CaCl 2 , KCl, or ISNT), but the r value between ISNT-N vs DM was lower than the r values obtained from the other extraction methods by the t test. Such results with ISNT are below those reported by Khan et al (2001), Sharifi et al (2007), and Klapwyk et al (2006). According to Sharifi et al (2007), the results obtained from ISNT were better than the ones with KCl in regard to correlation between soil N concentrations and potentially available N. The literature reported that N-amino sugars (the fraction that is extracted with ISNT) might be considered, overall, the labile fraction of soil organic N and it might be highly correlated with plant DM yield, N uptake (N up ), and response to N fertilization Barker et al, 2006).…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…In this case, r values between soil N and N up are not different among the methods (hot water, CaCl 2 , KCl, or ISNT), but the r value between ISNT-N vs DM was lower than the r values obtained from the other extraction methods by the t test. Such results with ISNT are below those reported by Khan et al (2001), Sharifi et al (2007), and Klapwyk et al (2006). According to Sharifi et al (2007), the results obtained from ISNT were better than the ones with KCl in regard to correlation between soil N concentrations and potentially available N. The literature reported that N-amino sugars (the fraction that is extracted with ISNT) might be considered, overall, the labile fraction of soil organic N and it might be highly correlated with plant DM yield, N uptake (N up ), and response to N fertilization Barker et al, 2006).…”
Section: Resultscontrasting
confidence: 76%
“…The ISNT-N concentration values (ranging from 16.8 to 316.9 mg dm -3 , Table 2) were lower than the values reported by other authors Klapwyk et al, 2006;Sharifi et al, 2007;Lawrence et al, 2009). The average ISNT-N values over 17 soil samples were 10.9 times, 6.9 times, and 3.4 times higher than the HW-N, CaCl 2 -N, and KCl-N values, respectively.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Thus, we normalized soil pH, SOM, Solvita CO 2 respiration, and NO 3 -N levels of each of the plots at each sampling date and year in reference to the first initial value of the first year, as was done by Klapwyk et al (2006) and Sadeghpour et al (2016). First, the average of the initial values of each parameter was determined, and the values of each plot were added or subtracted to reach a similar initial value for all the plots.…”
Section: Discussionmentioning
confidence: 99%
“…In 102 on‐farm N‐response experiments, the ISNT was significantly related to crop N requirement and was the most powerful predictor of error in yield‐based N recommendations (Mulvaney et al, 2006). There is growing evidence from N‐response evaluations that the ISNT can be used successfully for manure and fertilizer N management (Klapwyck and Ketterings, 2006; Klapwyck et al, 2006; Ruffo et al, 2006; Williams et al, 2007), although misinterpretations have occurred when other factors were neglected that affect crop N uptake or soil N availability, such as plant population, residue C input, soil acidity, or a deficiency of P or K.…”
Section: Resultsmentioning
confidence: 99%